Efektifitas Pengetahuan Ibu Balita Terkait Gizi Seimbang Balita Untuk Mencegah Stunting Melalui Penyuluhan Di Gampong Kiran Krueng Jangka Buya Pidie Jaya - Ambia Nurdin; Nurhaliza Nurhaliza; Zamzami Zamzami; Amiruddin Amiruddin; Zakiyuddin Zakiyuddin; Ricky Dear Fitria; Fauzi Aldina; Hendra Cipta; Muhammad Haikal (Pusat Riset dan Inovasi Nasional, 2023)
Fulfillment of nutrition is very important for the growth and development of children, especially in the first 1000 days of life (HPK). Family, especially mothers play an important role in providing balanced nutrition, therefore mothers must have good knowledge about it. The purpose of this activity is to increase the knowledge of mothers of toddlers about balanced nutrition in toddlers. This activity was carried out in the village of Kiran Krueng. This study used a pre-experimental design method with the type of one group pretest-posttest design. The target in this study were the women of Kiran Krueng Village, Jangka Buya District, Pidie Jaya Regency. The questionnaire in this study was used to examine the effect of providing counseling about stunting on increasing the knowledge of women in Kiran Krueng Village, Jangka Buya District, Pidie Jaya Regency. The number of samples taken was 20 mothers. It is known that most of the respondents were female as many as 20 respondents with a percentage of 100%, while most of them were aged 25-30 years as many as 12 respondents with a percentage of 60%. The highest level of knowledge of mothers before being given counseling was in the moderate category, 7 people (35%). The highest level of knowledge of mothers after being given counseling was in the high category, 20 people (100%). The average level of knowledge of mothers before being given counseling was 2,05 and after being given counseling, it was 1,00. From these results it can be concluded that there were positive results from the counseling process carried out.